9 Long-term outcomes of adults with alcapa repair. (28th April 2017) - Ooues, G; Thorne, S; Bowater, S; Clift, P; Hudsmith, L
Abstract : Background: Anomalous left coronary artery from the pulmonary artery (ALCAPA syndrome) is a rare congenital abnormality, which, if untreated, can cause complications such as myocardial infarction, heart failure and death; only few untreated patients survive to adulthood. We sought to determine long-term outcomes of these patients in our Adult Congenital Heart Disease service. Methods: A retrospective review of case notes of patients with ALCAPA was performed, reviewing clinic letters, operation details, cardiac imaging and exercise tests. Results: We identified 8 patients (6 female) with mean age 26.3±6.2 years. Mean follow-up was 4.1 years (range, 18 months to 12 years). All patients have had surgical repair; one patient required concomitant mitral valve repair. Mean age at operation was 9.7 years (range, 3 months to 34 years old); 3 patients (38%) were operated as adults. At last clinic review, one patient had NYHA III symptoms, the rest were well (NYHA I). Mean peak oxygen consumption on cardiopulmonary exercise testing was 36±2.4 ml/kg/min (range 33.4 to 38.8 ml/kg/min, mean 93%±15.9% predicted, range 78% to 112%). All patients were in sinus rhythm and no ischaemia or arrhythmias were identified. 7 patients (88%) had good left ventricular function (mean EF 61%); 1 patient had mildly impaired function (EF 50%) due to an apical transmural infarction. Moderate mitral regurgitation was seen in 3 patients (38%) and all had normal aortic root size. Conclusion: We describe long-term outcomes of patients with ALCAPA syndrome. Postoperatively, the majority remain asymptomatic with good exercise capacity. Their left ventricular systolic function is good. Life-long follow up is warranted.